Dexmedetomidine Improves Cardiovascular and Ventilatory Outcomes in Critically Ill Patients: Basic and Clinical Approaches - Castillo, Rodrigo L.; Ibacache, Mauricio; Cortínez, Ignacio; Carrasco-Pozo, Catalina; Farías, Jorge G.; Carrasco, Rodrigo A.; Vargas-Errázuriz, Patricio; Ramos, Daniel; Benavente, Rafael; Torres, Daniela Henríquez; Méndez, Aníbal (Frontiers in Pharmacology, 2020)
Dexmedetomidine (DEX) is a highly selective α2-adrenergic agonist with sedative and analgesic properties, with minimal respiratory effects. It is used as a sedative in the intensive care unit and the operating room. The opioid-sparing effect and the absence of respiratory effects make dexmedetomidine an attractive adjuvant drug for anesthesia in obese patients who are at an increased risk for postoperative respiratory complications. The pharmacodynamic effects on the cardiovascular system are known; however the mechanisms that induce cardioprotection are still under study. Regarding the pharmacokinetics properties, this drug is extensively metabolized in the liver by the uridine diphosphate glucuronosyltransferases. It has a relatively high hepatic extraction ratio, and therefore, its metabolism is dependent on liver blood flow. This review shows, from a basic clinical approach, the evidence supporting the use of dexmedetomidine in different settings, from its use in animal models of ischemia-reperfusion, and cardioprotective signaling pathways. In addition, pharmacokinetics and pharmacodynamics studies in obese subjects and the management of patients subjected to mechanical ventilation are described. Moreover, the clinical efficacy of delirium incidence in patients with indication of non-invasive ventilation is shown. Finally, the available evidence from DEX is described by a group of Chilean pharmacologists and clinicians who have worked for more than 10 years on DEX.